Exploring factors influencing competencies of scientific laboratory technicians and recommendations for improvement: A case study of a Scientific Laboratory based in a resource constraint setting - Kachambwa, Paidamoyo (Department of Human Biology, 2025)
Research in Africa and on African data is booming, seeing an increase in scientific projects conducted and products created. This significantly contributes to the bioeconomy, where establishing scientific laboratories is a key strategy. It is essential to ensure that there is competency, that is, the necessary knowledge applied when designing and implementing solutions. This produces quality outputs that attract funding and business. Technicians are key as they complete core functions that directly affect outputs. There are limited studies on scientific laboratory technicians in resource constraint settings, handling diverse projects, that focus on understanding underlying factors influencing their competencies. Influences were investigated in a transdisciplinary manner. Learning theories focused on how the adults learn (Knowles), their self-efficacy (Bandura) and their Community of Practice (Lave and Wenger). While Systems theory overlayed and focused on what a viable system should look like, Viable Systems Model (Beer). Focus groups were conducted with the technicians, managers, and senior managers. From thematic analysis, eight themes emerged: Communication, Contextual factors, Education, Hierarchy, Interpersonal, Leadership, Operational systems, and Organizational climate/culture. A central theme underlying all of the themes was Leadership, that is, how leadership influences and impacts the other themes. Surveys were conducted to triangulate findings and determine central tendencies. Key overall findings were from the senior managers. They sit in a significant position that influences the emerged themes and can action change. Although the senior managers understood and valued the different influences, they were less aware of the underlying factors, interactions, and resulting adverse effects. Overall recommendations were related to training and awareness at different hierarchy levels. For technicians and managers, frame how to differentiate between them viewing themselves as incompetent versus being in a hindering environment. For managers and senior managers, frame how different factors interact and influence technicians' competencies and resulting adverse effects. In Africa and abroad, this is replicable in scientific laboratories that conduct diverse scientific work, and this aids in developing the necessary contextual leadership training.